Pressure Measurements on a Deforming Surface in Response to an Underwater Explosion in a Water-Filled Aluminum Tube. (2001) - Chambers, G.; Sandusky, H.; Zerilli, F.; Rye, K.; Tussing, R.; Forbes, Jerry
Abstract : Experiments have been conducted to benchmark DYSMAS computer code calculations for the dynamic interaction of water with cylindrical structures. Small explosive charges were suspended using hypodermic needle tubing inside Al tubes filled with distilled water. Pressures were measured during shock loading by tourmaline crystal, carbon resistor and ytterbium foil gages bonded to the tube using a variety of adhesives. Comparable calculated and measured pressures were obtained for the explosive charges used, with some gages surviving long enough to record results after cavitation with the tube wall.